Corporate Governance and Regulation : Can There Be Too Much of a Good Thing? - Bruno, Valentina G. (World Bank, Washington, DC, 2012)
For a large number of companies from different countries, the authors analyze how company corporate governance practices and country regulatory regimes interact in terms of company valuation. They confirm that corporate governance plays a crucial role in efficient company monitoring and shareholder protection, and consequently positively impacts valuation. They find substitution in valuation impact between corporate governance measures at the company and country level, with a possibility of over-regulation. Corporate governance appears more valuable for companies that rely heavily on external financing, consistent with the hypothesis that the main role of corporate governance is to protect external financiers.